Sex steroid hormone residues in milk and their potential risks for breast and prostate cancer - Gao, Pengyue; Li, Chengyi; Gong, Quan; Liu, Lian; Qin, Rui; Liu, Jiao (Frontiers in Nutrition, 2024)
Milk was a source of important nutrients for humans and was especially important for children and adolescents. The modern dairy animal production pattern had contributed to residual sex steroid hormones in milk. When this milk was consumed by humans, these hormones entered the body leading to hormonal disruptions and potentially increasing the risk of various types of cancers. This article reviewed the presence of residual sex steroid hormones in milk, their potential risks on human health, and their possible association with the incidence of breast and prostate cancer. The potential linkage between dairy consumption and these cancers were described in detail. The hormones present in dairy products could affect the development and progression of these types of cancer. Sex steroid hormones could interact with different signaling pathways, influencing carcinogenic cascades that could eventually lead to tumorigenesis. Given these potential health risks, the article suggested appropriate consumption of dairy products. This included being mindful not just of the amount of dairy consumed, but also the types of dairy products selected. More scientific exploration was needed, but this review provided valuable insights for health-conscious consumers and contributed to the ongoing discussion on dietary guidelines and human health.